Effects of Increasing Farmed Salmon Intake to the Recommended Fish-Intake Amounts on Lipid Profile in Young Women: An 8-Week Intervention Study - Zofia Utri-Khodadady; Dominika Głąbska (Nutrients, 2024)
Background/Objectives: Habitual dietary changes that could help reduce the potential consequences of excessive body mass, such as hyperlipidemia and increased cardiovascular disease risk, are needed. The aim of this study is to assess the impact of a farmed-salmon-based dietary intervention on lipid profile parameters in young women with excessive body mass. Methods: The 8-week intervention involved 38 pair-matched women aged 18–30 years with excessive body weight defined as BMI ≥ 25.0 kg/m2. Participants were randomly assigned to the intervention (200 g of smoked salmon weekly) or the control group. Lipid profile parameters (total cholesterol (TC), high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides (TAG)), as well as atherogenic indices (Atherogenic Index of Plasma (AIP), Atherogenic Coefficient (AC), Cholesterol Index (Cholindex), Castelli Risk Index 1 (CRI-1), Castelli Risk Index 2 (CRI-2) and the TAG/HDL ratio) were assessed before, during, and after the intervention. Results: At baseline, 47% of participants had at least one of the lipid profile parameters outside the recommended range. No statistically significant differences were observed in the TC, HDL, non-HDL, LDL, or TAG concentrations or in the various atherogenic indices between the intervention and the control group after the 8-week-long intervention. However, differences in the change of the LDL concentration were noted, with a decrease of 8.2 ± 20.7 mg/dL in the intervention group compared to an increase of 9.5 ± 20.0 mg/dL in the control group (p = 0.011), as well as in the change of the Cholindex for which a median decrease of 4.4 mg/dL was noted in the intervention group, while a median increase of 0.8 mg/dL in the control group was observed (p = 0.040). Additionally, across participants with a waist-to-height ratio (WHtR) greater than 0.5, an increase of 50.0 ± 68.3 mg/dL in the intervention group and a decrease of 8.6 ± 56.6 mg/dL in the control group was noted for the TAG concentration change (p = 0.040). ...